2003
DOI: 10.1542/peds.112.4.896
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Aminoterminal Pro Atrial Natriuretic Peptide and Aminoterminal Pro Brain Natriuretic Peptide in Healthy Neonates: Marked and Rapid Increase After Birth

Abstract: The N-ANP and N-BNP plasma concentrations in healthy neonates showed a marked increase during the first days of age, suggesting that ANP and BNP have physiologic roles in the perinatal circulatory change from fetus to neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 25 publications
8
71
2
3
Order By: Relevance
“…This data is supported by the work of Hammerer-Lercher et al and Bakker et al [8,9] who showed NT-proBNP to be significantly higher in plasma from cord blood than in maternal plasma. N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13]. Our data differs from that reported by Rauh et al [13] and Koch et al [26].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This data is supported by the work of Hammerer-Lercher et al and Bakker et al [8,9] who showed NT-proBNP to be significantly higher in plasma from cord blood than in maternal plasma. N values in previous studies have been far too small to reliably define reference intervals for males and females at each age group [8][9][10][11][12][13]. Our data differs from that reported by Rauh et al [13] and Koch et al [26].…”
Section: Discussioncontrasting
confidence: 94%
“…Renal function has also been shown to influence the optimal cut-off points of NT-proBNP and BNP for the diagnosis of cardiacrelated dyspnoea [5]. Adult reference intervals are available in the literature [6,7] and recently Hammerer-Lercher et al and Bekker et al [8,9] [10][11][12][13]. All these studies have been performed on very small numbers of children at any one age group.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Studies in adults have shown that NT-proBNP is a more sensitive and more specific marker for ventricular dysfunction than the biologically active BNP. 24,25 Previous studies in healthy full-term infants showed that the plasma BNP level rapidly rises after birth, reaching its peak at day 2-3 of life [26][27][28] and a high plasma BNP level correlates with HsPDA. A decline of BNP level is noted after PDA is closed by indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to provide normative values for term and preterm infants (6,15). BNP and NT-proBNP concentrations rise at birth in normal healthy infants, level off at 3-4 d, and then fall steadily to stable but low levels in infancy (12,16). In several studies, the method of delivery of the newborn did not influence natriuretic peptide levels (17,18).…”
Section: Natriuretic Peptidesmentioning
confidence: 94%
“…These properties make natriuretic peptides attractive in the identification of congestive heart failure. Given that the serum half-life of BNP is longer than that of ANP, and that the former more accurately reflects cardiac function, BNP or the inactive N-terminal fragment of BNP (NT-proBNP) is generally preferred as a cardiac biomarker (11,12). When their application in adult medicine was found to show promise, research began to be directed toward the potential use of natriuretic peptides in neonatal medicine.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%